Uji kinerja mesin pengupas buah pinang kering menggunakan mekanisme pengupas tipe impact rotary poros horizontal - Iman Syahrizal; Daud Perdana (Universitas Muhammadiyah Metro, 2022)
Indonesia was one of the exporting countries of betel nut, lately the selling price of betel nut has increased. Betel nut that has a high selling price, was an old betel nut that has been dried. Various forms of betel nut that were sold in the market include whole betel nut, split betel nut and sliced betel nut. The purpose of this study was to find out the effect of the spin speed of the peeling mechanism on the timing and peeling result, and to find out the best interaction between the spin speed and the number of peeling rods that able to producing the best peeling efficiency. The method used in the study was a randomized design experiment consisting of two factors: spin speed (1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm) and the number of peeling rods (12, 18 and 24) with 12 testing interactions. The main parameter observed was the percentage of peeled fruit with whole condition. The performance test result proved that the increase of the spin speed peeling mechanism has an effect on the efficiency of time, when the speed spin of the peeling mechanism increases, the time it takes to peel the dried betel nut was decreases. But this condition was not directly proportional to the increasing percentage of dried betel nut that was whole peeled. The best peeling interaction was at a speed of 1400 rpm, with 18 peeling rods. This interaction produced peeling efficiency, 88% of whole peeled fruit, 12% of split peeled fruit and 0% of the unpeeled fruit.